The Relationship Between Parenting Style and the Peer Role with Adolescent Pregnancy Prevention Behavior - Roswita Rugaya Handayani Sebleku; Euvanggelia Dwilda; Lilik Djuari; Azimatul Karimah (Jurnal sosial dan sains, 2023)
Background: Adolescent pregnancy occurs in Approximately 12 million girls aged 15–19 years and approximately 777,000 girls under 15 years of age give birth each year in developing countries. The most of adolescent pregnancies occur every year, 50% of whom are aged 15-19 years, namely at least 21 million pregnancies and it contributes to maternal and child mortality rates. In Indonesia, it is estimated that around 1,220,900 women are married before the age of 18, placing Indonesia in the 10 countries with the highest absolute number of child marriages in the world). Purpose: To analyze the relationship between parenting styles and the role of peers regarding sexuality with adolescent pregnancy prevention behavior in the Autaqnapoq Health Centre Working Area. Method: This type of research uses an observational research design with a cross-sectional approach and instrument used is a questionnaire. The population in this study were all adolescents in the Autaqnapoq Health Centre Working Area. The sample in this study was 93. using purposive sampling techniques. The data was analyzed with Spearman rho test analysis. Results: the research showed that there is a relationship between parenting style with adolescent pregnancy prevention behaviour (p<0.001, r = 0.343). and there is a relationship also between the role of peers with adolescent pregnancy prevention behavior (p<0.000 and r = 0.357). Conclusion: The relationship between parenting styles and the role of peers with Adolescent pregnancy prevention behavior in the Autaqnapoq Lembata Health Centre Working Area.